Teaching Production Écrite Débutante Using Interactive Quizziz Game Learning Media - Evi Eviyanti; Isda Pramuniati; Irwandy Irwandy; Wahyuni Sa’dah (BIRCU, 2021)
The Covid-19 pandemic forces a social distancing policy or in Indonesia it is better known as physical distancing to minimize the spread of Covid-19. Universitas Negeri Medan as one of the LPTKs responded with a policy of learning from home, through online learning with the use of information technology. The objectives of this study were to: (1) develop teaching materials based on Quizziz interactive game learning media in teaching Production Écrite Débutante, (2) assessing the feasibility of teaching materials based on Quizziz interactive game learning media in teaching Production Écrite Débutante. This development research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research instrument used was a questionnaire and validation instruments for material experts and the design of teaching materials. Based on the results of the assessment by teaching material experts Production Écrite Débutante. Based on interactive game learning media Quizziz that was developed has content feasibility, namely the average score of 91.33%.very good), the feasibility of presenting the average score of 94.54%. (Very good), and the linguistic aspect obtained an average score of 94.61%. (Very good).The average score of the expert's assessment of teaching material design obtained 85.9% (Good). Based on the results of the validation, it shows that the teaching materials Production Écrite Débutante which has been developed to meet the demands of learning needs. Researchers limit the problem to the process of developing teaching materials based on interactive quizziz game learning media in teaching Production Écrite Débutante.